Faktor Risiko Kualitas Hidup Lansia Penderita Hipertensi - Prastika, Yuniar Dwi; Siyam, Nur (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2021)
Background: The Bandarharjo Primary Healthcare Center was become primary healthcare center with the highest cases of hypertension in Semarang City until November 2020. The working area of Bandarharjo primary healthcare center consisted of 4 villages with cases of hypertension in the elderly on January-February 2021 was 400 cases. The aim of the research was to determine the factors that affect the quality of life in elderly people with hypertension. Methods: The type of this research was observational analytics with cross sectional design. The research sample were 85 using purposive sampling. The instruments used were the WHOQOL-BREF questionnaire, the IPAQ Short Form questionnaire, and the MMAS-8 questionnaire. Data were analyzed with chi square test, fisher test, and logistic regression. Results: Variables that associated to the quality of life in the elderly with hypertension in this study were employment status variables (p=0.007), comorbidities (p=0.022), physical activity (p=0.021), and medication adherence (p=0.038). The factors that most influenced the quality of life in elderly people with hypertension were work status, comorbidities, and medication adherence. Conclusion: Occupational status, comorbidities, and medication adherence were the factors that most influence the quality of life in elderly people with hypertension.